Cardioprotective effects of Galium verum L. extract against myocardial ischemia-reperfusion injury. (19th October 2020) - Bradic, Jovana; Jeremic, Nevena; Petkovic, Anica; Jeremic, Jovana; Zivkovic, Vladimir; Srejovic, Ivan; Sretenovic, Jasmina; Matic, Stevan; Jakovljevic, Vladimir; Tomovic, Marina
Abstract: The aim of our study was to determine a chemical composition of methanol extract of Galium verum as well as to assess its effects on functional recovery and redox status of isolated rat heart after ischemia. Rats were divided into control and G. verum group, which included animals treated with 500 mg/kg of methanol extract of G. verum for 28 days. Parameters of heart function and oxidative stress markers were estimated. Cell morphology was evaluated by hematoxylin and eosin (HE) staining. Our results demonstrated for the first time that G. verum extract preserved cardiac contractility, systolic, and diastolic function as wells as structural damage of the heart after ischemia. Furthermore, G. verum extract modulated the activity of antioxidant enzymes and alleviated the production of pro-oxidants.